Kajian Beyond Use Date Sediaan Injeksi di Salah Satu Rumah Sakit Kota Bandung Tahun 2024 - Rizkita Nur Ainun; Eli Halimah; Julisiana Sanggelorang (Asosiasi Riset Ilmu Kesehatan Indonesia, 2025)
Beyond Use Date or BUD is the time limit for a non-sterile or sterile mixed preparation not to be stored and used, calculated from the date or time of compounding. BUD indicates the time limit for the preparation to be in a stable state so it is very necessary to determine the BUD time. This article aims to review BUD information on 20 types of injection preparations in one of the Bandung City Hospitals conducted in 2024 using information collection methods from various sources such as related drug brochures, LexiDrug, and Drug Information Handbook. The results of the study of 13 therapeutic classes with 20 types of injection preparations show that each sterile preparation has different characteristics (active substance, solvent, dosage form and its components, duration of therapy, and storage), thus affecting the stability after reconstitution of each preparation, both those determined by each pharmaceutical industry and information obtained from LexiDrug and Drug Information Handbook. The results of this study can be used as a reference in making more applicable guidelines in determining the BUD of injection preparations in one of the Bandung City Hospitals.